Crystal violet reactions of coagulase negative staphylococci. - Freeman, R (1994)
Twenty four reference strains and 112 clinical isolates of coagulase negative staphylococci (CNS) were examined for their reactions in the crystal violet test. Some species gave a white reaction and others a purple reaction. Results were consistent and reproducible and each species gave only one pattern of crystal violet reaction. Within the limited variety of species represented in the clinical isolates, Staphylococcus saprophyticus and S haemolyticus gave crystal violet purple reactions, in contrast to S epidermidis, which always gave a white reaction. Investigations suggested that the mechanism of the crystal violet test in S haemolyticus may be similar to that previously described in S aureus. Further work is needed to characterise the ability of crystal violet to modify S epidermidis and other central nervous system species. The crystal violet reaction, which has strong associations with invasiveness, phage group susceptibilities, colonisation persistence abilities, and nosocomial origin in S aureus may also be useful in studies of CNS disease.